The International Criminal Court and the Quest for Global Justice their Challenges and Prospects - Alni, Zainab Ahmed; Jasim, Rasem Mseer; Turki, Mohammed; Jasim, Bushra Abd Al-Lattif (Journal of Ecohumanism, 2024)
Background: The establishment of the International Criminal Court (ICC) was motivated by the need to confront severe international crimes and address the lack of accountability within national legal systems. Nevertheless, the role and effectiveness of this phenomenon have been topics of ongoing discussion among the global community. Objective: The article aims to analyze the many problems encountered by the International Criminal Court (ICC) in its pursuit of delivering justice worldwide while also exploring the potential outlook for its future position within the broader framework of the international justice system. Methods and Materials: This study included a thorough examination of ICC case law, the involvement of member states, and the concerns associated with the International Criminal Court. Additional insights into the activities of the Court and its perceived strengths and shortcomings were obtained via qualitative interviews conducted with international law experts and practitioners. Results: The study’s results demonstrate that the International Criminal Court (ICC) has achieved significant progress in ensuring persons’ responsibility for severe international offences. Nonetheless, the organization encounters significant obstacles, such as geopolitical influences, concerns over intergovernmental collaboration, and inquiries about its credibility and inclusiveness. Despite these problems, an increasingly prevalent agreement exists about establishing a resilient international judicial institution. Conclusion: It can be said that the International Criminal Court (ICC) continues to have a significant position within the framework of global justice. Despite encountering several difficulties, given the implementation of appropriate reforms and sustained backing from the global community, it could assume a more substantial role in upholding accountability and justice worldwide.